A Fireside Chat with Raj Gupta: What It Takes to Create Long‐Term Value. Issue 2 (2nd July 2019) - Gupta, Raj
Abstract : The chairman of two public companies (and former chair and CEO of Rohm and Haas) draws on his experience as a director of five private and 15 public companies in discussing the challenges and opportunities facing today's corporate boards. Perhaps the most formidable challenge is the pace of technological change, which is making business models 'in all industries and countries' obsolete and forcing companies to adapt much more quickly than in the past. Along with the risk of obsolescence is the increase in 'reputational risk' associated with an 'information age' in which companies are forced to monitor the nearly continuous flow of fact, hearsay, and outright fabrication. The author recommends that public company boards adopt a new 'partnership' model. Besides ensuring an 'ethical tone at the top, ' corporate directors should aim to become partners with the senior management team by playing more active roles in strategic planning, risk management, and the design of performance evaluation and incentive pay systems. In the most striking departure from current practice, the author urges directors to seize the opportunity created by the 'reconcentration' of ownership of U.S. public companies by actively engaging large institutional investors in a strategic dialogue about the companies' strengths and vulnerabilities. In so doing, proactive directors can help their management teams preempt shareholder activists and create long‐run value by creating a more effective two‐way channel of communication, one with the potential to give management more confidence when undertaking large strategic investments with longer‐run payoffs.